PENGARUH PARTISIPASI MANAJER TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Ikromi Abd Ghani HSB; Dovi Septiari (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2018)
The development of the business environment in globalization era has been triggered an increasingly tight business competition. Every companies who have an established its own strategies to manage a variety of information, human resources, allocation of funds and others. Accounting information system is a great resources that very valuable to an organization for the smoothness management of the company’s financial and decision making wheter it is to long term and short term, however there are several aspect that can be a factors the effectiveness of the accounting information system, that is manager’s participation. The research is aimed to proves that manager’s participation and manager’s involvement had a positive influence on the effectiveness of accounting information system (AIS) at manufacturing company, especially in the industrial zone Batamindo Mukakuning Batam City. The research method is using regression analysis to proves are the manager’s participation (independent variable) and manager’s involvement (independent variable) gives effect to the effectiveness of information system (dependent variable) or not. The result of this research is shows that variable of manager’s participation and manager’s involvement has a significant influence to the effectiveness of information system. The method is using purposive sampling is done by taking a sampling of the population according to certain criteria.